Geometric patterns of the Papua crown: A culturally inclusive approach to mathematics learning - Lestari, Nining Puji; Nengsih, Luluk Wahyu; Pagiling, Sadrack Luden; Yamin, Ade; Rosadi, Asep (Journal on Mathematics Education, 2025)
Embracing inclusivity and integrating cultural artifacts into mathematics teaching and learning has sparked the attention of many researchers for decades. Despite these conceptual advancements, the design and implementation of inclusive mathematics instruction in Papua, Indonesia, remains limited. Mathematics teaching and learning in Papua are still primarily dominated using government-provided textbooks. Addressing this void, this article discusses the use of Papua Crown as an inclusive mathematics learning medium due to its relevance to learners' daily lives. We highlight the exotic and rich patterns of the Papua Crown, which can be utilized to teach elementary school mathematics, particularly geometry. We employed an ethnographic approach by conducting observations with the artisans and users of the Papua Crown, interviews with two artisans, a museum curator, an archaeologist, and an anthropology lecturer, and documentation. We analyzed the connection between the geometric patterns in the Papua crown and the geometric concept that the teacher can potentially utilize in their practice. The findings elucidate that there are three geometric patterns in the Papua Crown: the triangle, symbolizing the human spiritual relationship with nature and God; the square, representing beliefs and ways of life based on nature; and the circle, personifying the life cycle of Papuan society. We hypothesize that Papua Crown can provide meaningful and engaging mathematics teaching and learning, as learners can identify existing patterns in geometry, particularly 2D shapes. Third, using geometry patterns from the Papua Crown in teaching and learning mathematics is predicted to assist learners in learning mathematical concepts contextually and appreciate culture by constructing knowledge from their experiences. This study is expected to contribute significantly to the development of a culturally inclusive mathematics learning that enables learners to understand mathematics concepts and honor the pluralism of Indonesian society.